The Spatiotemporal Pattern of Degeneration in the Cerebellum of the Wobbler Mouse. Issue 4 (April 2016) - Saberi, Darius; Ott, Bastian; Dahlke, Carolin; Matschke, Veronika; Schmitt-John, Thomas; Theiss, Carsten
Abstract : Amyotrophic lateral sclerosis (ALS) is a common neurodegenerative disease that affects motor neurons in the spinal cord and motor cortex. Various mouse models have been used to investigate the progression of the pathology of sporadic and familial ALS. Degeneration in the spinal cord and motor cortex in the Wobbler mouse model of sporadic ALS have been documented, but alterations of the cerebellum during disease progression have not been well characterized. We analyzed neurodegeneration and inflammatory responses in the cerebellar cortex of preclinical (p20), clinical (p40), and late (p60) stages in these mice. We did not identify evidence of neuron cell death, but we observed an inflammatory response detected by IL1B and TNFA expression by quantitative PCR, increased activated microglia and astrocytosis by immunohistochemistry, and ultrastructural abnormalities in the cerebella of Wobbler mice at late stages. These alterations may be caused by protein aggregations and variations in the distribution of cytoskeletal proteins; they might be reflected in the early manifestation of head tremor, which precedes motor deficits in these mice. Thus, we conclude that, in addition to the motor cortex and spinal cord, the cerebellum is affected by neurodegenerative and inflammatory processes in the Wobbler mouse model of ALS.